2005
DOI: 10.1103/physrevb.72.064111
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect on the soft-mode dynamics ofSrTiO3studied by Raman scattering

Abstract: The oxygen isotope effect on the soft-mode dynamics in quantum paraelectric SrTi͑ O atoms are 0.23 ͓STO18-23͔ and 0.32 ͓STO18-32͔, which are less than the critical value x c ͑=0.33͒. In STO18-32, whose exchange rate is just below x c , the soft E u mode shows hardening behavior in a low-temperature region indicating the onset of local ferroelectric order. On the other hand, the soft E u mode in STO18-23 does not show any hardening behavior until 0 K. The enhancement of the inhomogeneity in the crystal by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…However, previous studies have reported that the soft mode can be observed by Raman scattering via local symmetry breaking even in the centrosymmetric phase. [28,29] In the present study, the soft mode in the high-temperature region might be detected through the local noncentrosymmetric distortion in PMN. To facilitate quantitative discussions, we fitted the spectra in the same way as the low-temperature spectra.…”
Section: (A-c)] In Addition To the Lowest Wavenumber Component [Red Lmentioning
confidence: 97%
“…However, previous studies have reported that the soft mode can be observed by Raman scattering via local symmetry breaking even in the centrosymmetric phase. [28,29] In the present study, the soft mode in the high-temperature region might be detected through the local noncentrosymmetric distortion in PMN. To facilitate quantitative discussions, we fitted the spectra in the same way as the low-temperature spectra.…”
Section: (A-c)] In Addition To the Lowest Wavenumber Component [Red Lmentioning
confidence: 97%
“…The temperature dependence of the soft mode in such systems has been observed to exhibit an anomaly around the FE transition temperature -it softens upon cooling and either saturates or exhibits an upturn below the transition temperature. [8,10,15] The abrupt jump observed here might be related to the enhanced electric susceptibility and correlation length around the transition temperature (see discussions later), although its exact mechanism requires further study. In bare NbSTO there is no net electric polarization at T < 50 K because the directions of local FE moments are determined by that of the local symmetry breaking field, which varies randomly in space.…”
mentioning
confidence: 99%
“…Such inversion symmetry breaking activates the extra soft mode in Raman spectrascopy and induces local FE order. [8,10,15,[25][26][27] Therefore, in the case of NbSTO, the observed extra Raman mode originates from the micro regions around the Nb dopants. The reason it is only seen in substantially doped NbSTO is because suf- Raman shift and (c) half width at half maximum (HWHM).…”
mentioning
confidence: 99%
“…The light scattering method is adequate for the dynamical study of the phase transition because it detects the spectra of the lattice modes as a function of both frequency and wave vector near the point in the Brillouin zone. The purpose of the present paper is to review the recent light scattering studies on the dynamical property of the oxygen-isotope induced ferroelectric phase transition in STO18 including the partially substituted ones [14][15][16][17][18][19]. The experiments are described briefly in next section, and the present experimental results in the following section are compared with the other previous experimental results in the final section.…”
Section: Soft-mode In Quantum Paraelectric Srtio 3 [393]/169mentioning
confidence: 90%